Pengaruh E-Commerce dan Pengetahuan Kewirausahaan terhadap Minat Berwirausaha Fresh Graduate dengan Modal Sebagai Variabel Moderating - Sitorus, Isnaini Faraz Azis Ilmi; Nawawi, Zuhrinal M.; Jannah, Nurul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of e-commerce and knowledge on the interest in entrepreneurship for fresh graduates with capital as a moderating variable. This research uses a quantitative approach. The data was collected using a questionnaire with a simple random sampling technique which was distributed to fresh graduates at state campuses in Medan City, namely (USU, UNIMED, and UINSU) with a sample of 99 people. The research results here show that E-Commerce has a positive and significant effect on Entrepreneurial Interests, Entrepreneurship Knowledge has a positive and significant effect on Entrepreneurial Interests, Capital can moderate the effect of E-Commerce on Entrepreneurial Interests and Capital can moderate the effect of Entrepreneurship Knowledge on Entrepreneurial Interests. and based on the E-Commerce F test and Entrepreneurial Knowledge have a simultaneous and significant effect on Interest in Entrepreneurship with the magnitude of the influence based on the coefficient of determination test that is equal to 41.6%. Keywords: E-commerce, Entrepreneurial Knowledge, Asset, Entrepreneurial Interest, Fresh Graduate.